Diagnosis of invasive fungal infections in hematology and oncology: guidelines from the Infectious Diseases Working Party in Haematology and Oncology of the German Society for Haematology and Oncology (AGIHO) - Ruhnke, Markus; Buchheidt, Dieter; Heußel, Claus Peter (Annals of oncology, 2012)
Invasive fungal infections (IFIs) are a primary cause of morbidity and mortality in patients with hematological malignancies. Establishing a definite diagnosis of IFI in immunocompromised patients is particularly challenging and time consuming, but delayed initiation of antifungal treatment increases mortality. The limited overall outcome has led to the strategy of initiating either ‘empirical’ or ‘preemptive’ antifungal therapy before the final diagnosis. However, diagnostic procedures have been vastly improved in recent years. Particularly noteworthy is the introduction of newer imaging techniques and non-culture methods, including antigen-based assays, metabolite detection and molecular detection of fungal DNA from body fluid samples. Though varying widely in cancer patients, the risk of IFI is highest in those with allogeneic stem cell transplantation and those with acute leukemia. The AGIHO presents recommendations for the diagnosis of IFIs with risk-adapted screening concepts for febrile episodes in patients with haemato-oncological disorders.